PRIBUMISASI HUKUM ISLAM DALAM PESANTREN - Aziz, M. Shohibul (USRATUNA: Jurnal Hukum Keluarga Islam, 2019)
Indigenization of Islam is the conceptointing out that Islam actually has its own distinctions that are different from Arabiancultures where Islam first emerged. To accomplish this concept, all elements of Arabian culture are gradually eliminated and then reformulate the elements of Indonesian indigenous cultures. This is the meaning of Islam in relation to tradition. Then, what if the relation between Islam and tradition is put into the real mof law? And do religious institutions especially Islamic schools (pesantrens) also experience enculturation ? This paper examines how pesantrens assesssocialcustoms and traditions as something that is not contrary to Islamic law, even pesantrens perpetuate the tradition on the ground that it is part of indigenization of Islamin the lives of local people. This practice is maintained because pesantrens discern that the transcendent nature of religious law should be connected with wisdoms of localcultures in order that dynamics and harmony could occur nwhen laws face time changes.